2013
DOI: 10.1002/da.22149
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Change in Anxiety Severity and Impairment During and After Treatment With Evidence-Based Treatment for Multiple Anxiety Disorders in Primary Care

Abstract: Background Coordinated Anxiety Learning and Management (CALM) is a model for delivering evidence-based treatment for anxiety disorders in primary care. Compared to usual care, CALM produced greater improvement in anxiety symptoms. However, mean estimates can obscure heterogeneity in treatment response. This study aimed to identify (1) clusters of participants with similar patterns of change in anxiety severity and impairment (trajectory groups); and (2) characteristics that predict trajectory group membership.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
(77 reference statements)
0
10
0
Order By: Relevance
“…A prior study examining the CALM cohort similarly found that being unemployed was associated with inconsistent partial symptom improvement (Joesch et al, 2013). Furthermore, our results fit well with numerous studies identifying higher rates of stress and psychiatric disorders in low SES patients (Abravanel and Sinha, 2014; McLeod and Kessler, 1990; Muntaner et al, 2004) .…”
Section: Discussionmentioning
confidence: 91%
“…A prior study examining the CALM cohort similarly found that being unemployed was associated with inconsistent partial symptom improvement (Joesch et al, 2013). Furthermore, our results fit well with numerous studies identifying higher rates of stress and psychiatric disorders in low SES patients (Abravanel and Sinha, 2014; McLeod and Kessler, 1990; Muntaner et al, 2004) .…”
Section: Discussionmentioning
confidence: 91%
“…Although these data indicate clear heterogeneity in patient responding, critical evaluation suggests that profiles derived from raw symptom scores may more strongly reflect differences in initial PTSD severity as opposed to variability in patterns of change per se. Furthermore, person‐centered techniques employed in existing research are generally ill equipped to isolate response trajectories that deviate from continuous mathematical functions (e.g., those involving rapid symptom fluctuations) …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, person-centered techniques employed in existing research are generally ill equipped to isolate response trajectories that deviate from continuous mathematical functions (e.g., those involving rapid symptom fluctuations). [44] Given these considerations, the current study reviewed archival records to evaluate heterogeneous profiles of recovery in veterans receiving PE through a specialty VAMC clinic. Latent profile analyses (LPA) of change in weekly symptom data (i.e., deviation from initial score) were used to identify discontinuous trajectories of responding across 10 weeks of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…For some conditions, linear change best described a given class; for others, a hyperbolic, quadratic, or higher-order polynomial change appeared to best characterize change. This provides further justification for using LPA in lieu of other computational methods that assume homogeneous patterns of change across classes (Joesch et al ., 2013). Further consideration of the underlying process of change in class membership is necessary.…”
Section: Discussionmentioning
confidence: 99%